Keeping the middle path: mainstreaming religious moderation through Islamic higher education institutions in Indonesia - Muhammad Nasir; Muhammad Khairul Rijal (Indonesian Journal of Islam and Muslim Societies, 2021)
The Ministry of Religious Affairs of Indonesia continues to voice religious moderation to mainstream a peaceful Islamic discourse. This article aimed at looking at religious moderation values from several Islamic higher education institutions in Indonesia. The focus of article aims to find a pattern of the implementation of moderation in Islam in Islamic universities. This article discusses to what extent Islamic higher education institutions internalize religious moderation values to students. By conducting qualitative research, this article explores 3 Islamic higher education institutions in Indonesia: Universitas Islam Negeri Maulana Malik Ibrahim, Universitas Darussalam Gontor Ponorogo, and Ma’had Aly As'adiyah. The result shows that higher education institutions play a critical role in inculcating religious moderation values through pesantren institutions. The Pesantren universities have a role in transmitting moderate Islamic values through their curriculum and various religious activities. This research reveals that religious moderation is implicated in these 3 Islamic universities. The curriculum is eclectic and reflects moderation values, such as national commitment, tolerance, non-violence, and local culture accommodation. This study concludes that the three pesantrenuniversities in Indonesia have a distinctive pattern of emphasizing moderation in the three areas: theoretical, practical, and ideological aspect.